An International Legal Framework of Food Security and Its Impact on Indian Legislation - Gupta, Divya; Kumari, Anjali (Journal of Ecohumanism, 2025)
This research paper explores the evolution of the international legal framework for food security and critically examines its profound influence on the development of domestic legislation in India. The right to adequate food, while not always explicitly named, is a fundamental human right embedded within the broader context of the right to an adequate standard of living. This study traces its normative development through key international instruments, beginning with the foundational principles of the Universal Declaration of Human Rights (UDHR) of 1948 and the legally binding provisions of the International Covenant on Economic, Social, and Cultural Rights (ICESCR) of 1966. It further analyzes the contributions of subsequent declarations and conventions, including the Universal Declaration on the Eradication of Hunger and Malnutrition (1974), the United Nations Convention on the Rights of the Child (UNCRC) of 1989, and the Convention on the Rights of Persons with Disabilities (CRPD) of 2006, which have progressively refined state obligations towards vulnerable groups. The paper also considers the role of the UN Sustainable Development Goals, particularly Goal 2: Zero Hunger, in shaping contemporary policy agendas. The central argument is that this evolving international framework has served as a crucial normative and moral catalyst for the transformation of food security from a policy objective into a justiciable legal right in India. The paper analyzes the impact of these international norms on Indian legislation, culminating in a detailed examination of the National Food Security Act (NFSA), 2013. By assessing the NFSA’s provisions in light of international standards, this research evaluates the extent to which India has translated its international commitments into enforceable domestic law, highlighting both the achievements and the persistent challenges in the realization of the right to food for all its citizens.